Dampak Toxic Relationship Bagi Remaja Kristen dalam Berpacaran - Ayek, Ayek; Cinta, Yesa (GRAFTA: Journal of Christian Religion Education and Biblical Studies, 2023)
Toxic relationships in dating are a problem often experienced by teenagers, including Christian teenagers. These unhealthy relationships are characterized by emotional manipulation, excessive control, constant conflict, and lack of healthy communication, which ultimately negatively impacts psychological, spiritual, and social well-being. Teens trapped in toxic relationships tend to experience stress, anxiety, and loss of self-confidence. Spiritually, toxic relationships can distance them from Christian values of love, patience, and respect for others, and reduce their involvement in the church community. Therefore, understanding the impact of toxic relationships on Christian teenagers is important to provide solutions in building healthier relationships. This research was conducted through a literature study of various related sources, including developmental psychology, interpersonal relationships from a Christian perspective, and factors that contribute to toxic relationships among adolescents. The results show that guidance based on biblical values, such as love, respect, and healthy communication, plays an important role in shaping more positive relationship patterns. In addition, support from family, church community, and education on healthy relationships are key factors in helping adolescents avoid and overcome the negative impacts of toxic relationships. This study makes a new contribution in understanding the importance of a spiritual-based approach in building harmonious relationships that are in line with Christian teachings. With better education on healthy relationships, it is hoped that Christian adolescents can live a more emotionally, socially and spiritually prosperous life.